iChain: Peer-To-Peer Machine Learning Powered by Blockchain Technology - Johnson, Caleb; Lu, Tao; Rivera, Pedro; McDonald, Devon; Pritchett, Samuel; Peng, Lu (Frontiers in Blockchain, 2021)
iChain is an application that was created to help meet the growing demand for machine learning. It allows users to pay those with powerful machines to run machine learning tasks for them, bypassing the need for a significant investment in a powerful computer to run it themselves. This is similar to services like a render farm. Our application functions using the Ethereum blockchain which ensures security and decentralization, as well as providing a platform for payment transactions. This article will discuss the background on machine learning and blockchain, the application, how it works, how the data moves through it, and how to use it. We hope our application will enable many without the funds to build or buy a powerful computer to experiment with and utilize complex machine learning tasks.